Case report of a successful term pregnancy following renal transplantation - Kodey, Prabhadevi; Bahadur, Badugu Rao; Srilatha, V.; Rao, G. Srinivasa; P., Sowjanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Pregnancy with renal disease is associated with high risk for both mother and fetus with adverse outcomes. Criteria for considering pregnancy in renal transplanted patients include good post-transplant health for 2 years, stable allograft function with a serum creatinine <1.5 mg/dl, absence of rejection, control of blood pressure, absence of proteinuria. Authors report a case of 26-year-old, primigravida had renal transplantation done in NRI Medical College and treated with immunosuppressive therapy with tablets Tacrolimus 1mg twice daily, Azathioprine 50mg twice daily, Prednisolone 10mg once daily and continued till delivery. Developed gestational hypertension treated with tablet Amlodipine 5mg once daily. Elective caesarean section done for contracted pelvis. Post-natal period was uneventful and discharged on immunosuppressive therapy and contraceptive advice. Post-renal transplantation pregnancy should have multidisciplinary approach for. With close medical and obstetric follow up, successful outcome for both mother and infant is possible.